Molecular Conductance Versus Inductive Effects of Axial Ligands on the Electrocatalytic Activity of Self-Assembled Iron Phthalocyanines: The Oxygen Reduction Reaction - Zagal-Moya, J; Zagal-Moya, J; Caroli-Rezende, M; Silva-Rojas, J; Silva-Rojas, J; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Ponce-Hormazabal, I; Onate, R; Gutierrez-Ceron, C; Gutierrez-Ceron, C (Elsevier Ltd, 2019)
The construction of self-assembled iron phthalocyanine (FePc) systems on gold electrodes modified by self-assembled monolayers (SAMs) is becoming an interesting strategy for obtaining electrocatalytic molecular building blocks for the oxygen reduction reaction (ORR). In this work, we have measured the conductance of pyridiniums axial ligands at the single molecule level using the scanning tunneling microscope-based break-junction method (STM-Break Junction) to study the role of the axial ligand on the activity of the self-assembled FePc systems on a gold electrode surface. The electron-pulling effect of pyridinium axial ligands is known to increase the electrocatalytic activity of FePc for the oxygen reduction reaction (ORR). We have used these systems as a platform for carrying out a comparative study for understanding the real influence of the proximal axial ligands. Further, these ligands act as molecular wires between the gold electrode surface and the FePc molecule. The pyridinium molecules were synthesized following a series of structural variations using a basic molecular backbone. From conductance measurements obtained for each pyridinium molecule, it was possible to establish that electron transport through each pyridinium does not influence the activity of FePc for ORR in alkaline media. In addition, the DFT calculations shows that the axial ligand in FePc modifies its catalytic activity by decreasing the binding energy of O2 to the Fe site. © 2019 Elsevier Ltd